Development of a Piston Ring Pack Model for Internal Combustion Engines - Αντωνόπουλος, Σπυρίδων (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ναυπηγών Μηχανολόγων Μηχανικών. Τομέας Ναυτικής Μηχανολογίας, 2017)
Internal combustion engines are widely used in industry. In the maritime industry, a variety of different combustion engines are used to provide propulsion and electric power. Typically, a conventional cargo ship operates with one large bore 2-stroke marine engine that is directly coupled with the propeller to provide the required thrust, while a set of two or more smaller 4-stroke engines generate the electricity for hotel loads, machinery operation, navigation systems, etc. Strict regulations regarding the emissions of the ships, as well as the need for the minimization of running and maintenance costs are important factors that dictate the development of technologically advanced IC engines. Moreover, reliability is critical, considering that safety at sea is of the utmost importance. The piston ring pack assembly in IC engines plays an essential role as it provides the necessary dynamic seal for the combustion chamber. Energy losses due to friction in the ring pack account for approximately 1.1 to 4 percent of the total energy loss in the engine. Thus, design for minimization of friction in ring packs is meaningful. Furthermore, design for minimization of the blow-by increases the engine’s efficiency while it reduces the unburned hydrocarbon emissions. Another important aspect of piston ring pack design is wear as ring replacement can be very expensive for large bore 2-stroke marine engines. On some occasions, extensive wear can also shorten the engine’s life. In the present study, a two-dimensional model for the simulation of the piston ring pack system has been developed. Physical formulation allows for the ring dynamics and gas dynamics to be coupled in an integrated model. This model is capable of predicting ring movement, gas pressure in both the back of the ring and the inter-ring volumes, and gas flow in the various crevices of the ring pack system. A simplified software model has been implemented for a 4-stroke gasoline engine and has been validated against literature data. In particular, given the land pressures and the ring motion, the present model is capable of calculating the pressure distribution acting on the ring generated by three different phenomena: pressure generation due to the gas in the ring-groove channel, pressure by the oil in the piston groove, and asperity contact pressure between the ring and its groove. The implemented model is also capable of calculating the gas flows through the ring groove channel and the ring gap. The validity of the model has been verified by comparisons with both the outputs of a similar published model and with experimental data.